An international breeding project using a wild potato relative Solanum commersonii resulted in two new frost-tolerant native potato cultivars for the Andes and the Altiplano - Arcos-Pineda, Jesus H.; del Rio, Alfonso H.; Bamberg, John B.; Vega-Semorile, Sandra E.; Palta, Jiwan P.; Salas, Alberto; Gomez, Rene; Roca, William; Ellis, David (Frontiers in Plant Science, 2024)
This breeding project initiated at the USPG in collaboration with Peruvian partners INIA, CIP, and local farmers sought to enhance cold hardiness and frost tolerance in native potato cultivars in Peru. The Andes and Altiplano are often affected by frost which causes significant reduction in yield; creating varieties with superior resilience is a critical undertaking. The goal was to transfer outstanding non-acclimated cold tolerance and acclimation capacity found in wild potato species Solanum commersonii (cmm). Breeding families segregating for cold hardiness were created using (a) a somatic hybrid cmm + haploid S. tuberosum (tbr) (cv. Superior, US variety from Wisconsin) as male and, (b) seven cultivars native to Peru of species S. tuberosum sbsp. andigenum (adg) as females. All plant materials were part of the USPG germplasm collection.Sexual seeds of each family were sent to Peru for evaluations under the natural conditions of the Andean highlands and Altiplano. The plants were assessed for their response to frost and genotypes showing exceptional tolerance were selected. Plants were also evaluated for good tuber traits, and yield. Initial planting involving ~2500 seedlings in five locations resulted in selecting 58 genotypes with exceptional frost tolerance, good recovery capacity after frost and nice tuber traits. Over the years evaluations continued and were expanded to replicated field trials in the harsher conditions of the Altiplano (Puno). All trials confirmed consistency of frost tolerance over time and locations, tuber quality and yield. After eight years, two advanced clones were considered for cultivar release because of their exceptional frost tolerance and superior field productivity that outyielded many of the established cultivars in the region. In November 2018, a new native cultivar named Wiñay, a Quechua word meaning "to grow" was released in Peru. In 2022, a second cultivar followed with the name Llapanchispaq (meaning "for all of us"). This project evidenced that a multinational, and all-encompassing approach to deploy valuable genetic diversity can work and deliver effective results. This is even more significant when outcomes can promote food security and sustainability in very vulnerable regions of the world.